Classical trigeminal neuralgia is associated with gephyrin and sodium voltage-gated channel alpha subunit 8 - Vieira, Alexandre R.; Sekula, Raymond F.; Deeley, Kathleen (Frontiers in Dental Medicine, 2023)
Trigeminal neuralgia is highly debilitating, and its etiology is still undefined. The goal of this work was to define associations between well-characterized trigeminal neuralgia cases and common genetic variants in the population. two hundred and fifty-seven individuals diagnosed with classical trigeminal neuralgia were compared to 865 individuals without classical trigeminal neuralgia and with an assessment for lower or higher pain threshold based on the amount of anesthetic required for routine dental treatment. Genotypes of 24 variants marking genes in the VGSC (voltage-gated sodium channels) or GABA (gamma-aminobutyric acid) pathways were obtained using TaqMan chemistry end end-point analysis. Chi-square was used for all comparisons with an alpha of 0.002. An association between classical trigeminal neuralgia and individuals requiring less or more anesthetic for routine dental treatments showed associations with SCN8A rs1601012 and GPHN rs723432 (p=0.0009 and p=0.0002, respectively). In conclusion, classical trigeminal neuralgia is associated with SCN8A and GPHN and markers rs1601012 rs723432 may be useful to determine individual risks for the condition.